Analisis Struktur dan Fungsi Tutunggulan di Desa Raharja: Kajian Struktur Pertunjukan dan Fungsi Folklor - Rizki Muhamad Fakih; Cut Nuraini; Een Nurhasanah (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study examines the structure and function of Tutunggulan performances in Raharja Village using Sims & Stephens' performance theory and Dundes' folklore function theory. The method used is descriptive analysis with a qualitative approach. Research data was obtained from observations, documentation, and interviews with Tutunggulan performers in Raharja Village. The results of the study show that 11 of the 13 performance structures of Tutunggulan in Raharja Village are present. Two indicators are not present in the Tutunggulan performance in Raharja Village because the Tutunggulan performance in Raharja Village is not a verbal performance but a musical performance and does not include text in its performance. Furthermore, 4 out of 6 indicators of folklore functions were found in the Tutunggulan performance in Raharja Village. The 2 indicators that were not fulfilled were (1) imposing social sanctions and punishments to encourage good behavior and (2) serving as a means of social criticism. A shift in the function of Tutunggulan was also found, from its original form as an activity of pounding rice to its current form as entertainment for the people of Raharja Village.